Efektivitas Penggunaan Alat Peraga Medan Magnet dalam Meningkatkan Literasi Sains Siswa Sekolah Dasar Kelas VI - Ariefka, Reza; Rosely, Annisa (LPPPI Publishing, 2025)
This study aims to measure the effectiveness of magnetic field teaching aids in improving the scientific literacy of sixth-grade elementary school students. The research method used is a true experiment with a pretest-posttest control group design. The research sample consisted of two classes, namely the experimental class that used magnetic field teaching aids and the control class that used conventional learning methods. Data were collected through pretest and posttest tests, then analyzed using normality tests, homogeneity tests, Independent Sample t-tests, and N-Gain tests with the help of the SPSS version 25 application. The results showed that the average pretest score in the experimental class was 69.20, while in the control class, it was 62.13. After being given treatment, the average posttest score in the experimental class increased to 84.67, while in the control class, it only increased to 75.20. The results of the hypothesis test showed a significance value of 0.013, which means that there was a significant difference between the experimental class and the control class. In addition, the results of the N-Gain effectiveness test with a value of 56.7% showed an increase in students' scientific literacy skills using magnetic field teaching aids.